2016
DOI: 10.1038/srep31328
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanoparticles tuned thermal sensitive photonic polymer for biomimetic chameleon

Abstract: Among many thermo-photochromic materials, the color-changing behavior caused by temperature and light is usually lack of a full color response. And the study on visible light-stimuli chromic response is rarely reported. Here, we proposed a strategy to design a thermo-photochromic chameleon biomimetic material consisting of photonic poly(N-isopropylacrylamide-co-methacrylic acid) copolymer and plasmonic nanoparticles which has a vivid color change triggered by temperature and light like chameleons. We make use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…Gold nanoparticles (AuNPs) have long been generally employed as PA‐imaging contrast agents due to the LSPR effect, which allows their adjustable and excellent optical absorption . In addition, AuNPs can attain high photothermal conversion effect upon laser illumination and are highly biocompatible, have good chemical inertness, excellent physiochemical properties, and a high extinction coefficient . AuNPs have been synthesized as nanorods, nanoprisms, nanocages, nanospheres, nanostars, nanodisks, bipyramids and rhombic dodecahedra, nanoplates, nanoshells, nanotripods, and nanowreaths …”
Section: Inorganic Contrast Agentsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) have long been generally employed as PA‐imaging contrast agents due to the LSPR effect, which allows their adjustable and excellent optical absorption . In addition, AuNPs can attain high photothermal conversion effect upon laser illumination and are highly biocompatible, have good chemical inertness, excellent physiochemical properties, and a high extinction coefficient . AuNPs have been synthesized as nanorods, nanoprisms, nanocages, nanospheres, nanostars, nanodisks, bipyramids and rhombic dodecahedra, nanoplates, nanoshells, nanotripods, and nanowreaths …”
Section: Inorganic Contrast Agentsmentioning
confidence: 99%
“…The gold/silver nanoparticles coupled with the inverse‐opal‐responsive hydrogel increase the sensitivity of the temperature response and make it possible to show a full color response over the entire visible spectrum in the system (Figure a). It is also demonstrated that by increasing the temperature, a molecular conformation transformation of PNIPAM happens that induce conformation rotation from intermolecular hydrogen bond into intramolecular hydrogen bond …”
Section: Artificial Materialsmentioning
confidence: 99%
“…PNIPAM hydrogels as one of the well‐studied temperature‐responsive color‐changing systems have been coupled with plasmonic nanoparticles, since the latter induce a heat buildup in the hydrogel systems as a result of the light absorption. A design strategy for a thermo‐photochromic composite consisting of photonic poly( N ‐isopropylacrylamide‐ co ‐methacrylic acid) (P(NIPAM‐ co ‐MA)) copolymer and plasmonic nanoparticles has been proposed . The gold/silver nanoparticles coupled with the inverse‐opal‐responsive hydrogel increase the sensitivity of the temperature response and make it possible to show a full color response over the entire visible spectrum in the system (Figure a).…”
Section: Artificial Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart polymers that are capable of conformational changes in their network structure and swelling properties in response to one or two external stimuli, have recently become interesting materials in many research areas such as drug delivery, optical and electrical devices, sensors, and separation science [1][2][3][4][5][6][7]. Among them, those containing metal nanoparticles have received particular attention since they not only simply combine the advantageous properties of both metal complexes and polymers, but also show new attractive properties that do not appear in either [8,9]. For example, palladium nanoparticles embedded into thermo-responsive polymer exhibit a high catalytic stability with higher selectivity for allyl alcohol hydrogenation and cyclohexane oxidation reactions [10].…”
Section: Introductionmentioning
confidence: 99%